Differential dynamics of Aβ and tau oligomer synaptic binding may suggest diverse therapeutic targets for early vs. late Alzheimer's disease: Molecular and cell biology/synaptic disruption. (7th December 2020) - Marcatti, Michela; Krishnan, Balaji; Kayed, Rakez; Taglialatela, Giulio
Abstract: Background: At the basis of the Alzheimer's Disease (AD) cognitive decline there is the targeting of synapses by small Ab and tau oligomers, which results in synaptic dysfunction and later disruption that underscore disease progression. Recent failures of Aβ‐directed therapeutics in multi‐center clinical trials suggest that Ab may not be playing a critical role in later disease stages, when clinical features of AD become manifest; rather, tau, which occurs later in the AD brain, may be the primary synaptotoxic element at that advanced stage. While attention is being currently given to the development of tau‐directed therapies for clinical AD, the mechanisms by which tau becomes the prevalent driver of synaptic dysfunction at later disease stages is still unknown. Method: Synaptosomes were isolated from the human and mouse cortex and hippocampus and Aβ and tau binding evaluated ex vivo using a flow‐cytometry based approach employing fluorescence‐labeled preformed oligomers. Western blots were used to confirm flow‐cytometry results and electrophysiology measurements of hippocampal long‐term potentiation (LTP) used to evaluate functional outcome of oligomer synaptic impact. Result: Here we show that the binding of tau to both human and mouse hippocampus and cortex synaptosomes competes Aβ oligomers off the synapses, thus becoming the most prevalent and toxic oligomeric form. On the other hand, Aβ oligomers are not able to compete off tau oligomers thus suggesting that the mechanism is tau specific. Surprisingly, the presence of Aβ oligomers promotes tau synaptic binding and levels of tau that would normally fail to negatively affect LTP becomes effective in the presence of Aβ oligomers. Conclusion: These results suggest a previously unappreciated mechanism whereby as the levels of Aβ oligomers increase and tau oligomers appear during disease progression, tau oligomers becomes the prevalent toxic species at synapses. This mechanism is consistent with failure of Aβ‐targeting therapies in late AD and further support the credence of tau oligomers as the main culprit in clinically‐manifest AD. Supported by NIH/NIA grant R01AG060718